Hospital response to a case-based payment scheme under regional global budget: The case of Guangzhou in China. (January 2022) - Lai, Yi; Fu, Hongqiao; Li, Ling; Yip, Winnie
Abstract: Both developed and developing countries have been searching for effective provider payment methods to control health expenditure inflation. In January 2018, Guangzhou city in Southern China initiated an innovative case-based payment method for inpatient care under the framework of the regional global budget, called the Diagnosis-Intervention Packet (DIP). Contrary to the usual practice of the case-based payment, the DIP payment scheme includes a price adjustment mechanism through which the actual reimbursement for each case is determined ex post. By employing the difference-in-difference method and data from Beijing and Guangzhou, we evaluate the effects of the DIP payment on medical expenditures and provider behaviors. We find that total health expenditures per case have decreased by 3.5%, which is mainly driven by a substantial decrease in drug expenditures. It suggests that the DIP payment reform achieved a short-term success in slowing down the growth of health expenditures. However, the average point volume per case for local inpatients with social health insurance coverage has increased by more than 3%, primarily due to an increasing likelihood of performing at least one procedure. We also find suggestive evidence of up-coding. All these results suggest that healthcare providers have taken strategic behaviors in response to the DIP payment. These findings hold lessons for the ongoing payment reforms in China and other countries. Highlights: The Diagnosis-Intervention Packet (DIP) is an innovative payment method in China. It is a type of a case-based payment scheme under regional global budget. It has achieved a short-term success in slowing down health expenditure growth. But hospitals have increased treatment intensity after the DIP payment reform. We also find suggestive evidence of up-coding in response to the DIP payment.